Integral Transforms with Non-separated Variables and Discontinuous Coefficients - Yaremko, O.E. (Журнал математической физики, анализа, геометрии, 2013)
Multidimensional integral transforms with non-separated variables for discontinuous coefficients problems are constructed in the case where the coefficient discontinuities are on the parallel hyperplanes. Explicit kernel formulas for ideal coupling conditions are obtained. The basic integral transform identity is proved.